2017
DOI: 10.1111/cogs.12481
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Word Meaning Induction From Minimal Exposure to Natural Text

Abstract: By the time they reach early adulthood, English speakers are familiar with the meaning of thousands of words. In the last decades, computational simulations known as distributional semantic models (DSMs) have demonstrated that it is possible to induce word meaning representations solely from word co-occurrence statistics extracted from a large amount of text. However, while these models learn in batch mode from large corpora, human word learning proceeds incrementally after minimal exposure to new words. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 33 publications
5
143
0
Order By: Relevance
“…This is an interesting result by itself, as it demonstrates that learning about features of a novel concept can be achieved by presenting the respective novel words in the context of natural sentences, thereby extending the findings by Ouyang et al (2017) to another, more naturalistic learning scenario. Remarkably, this learning occurs even if the novel words do not directly correspond to an actual concept with which the learner already has experience, but they are instead textual chimeras created from two category members (Lazaridou et al, 2017). This result supports the distributional hypothesis that word meanings are at least partially determined by the linguistic context the words occur in (Harris, 1954;Landauer & Dumais, 1997;Lund & Burgess, 1996;Sahlgren, 2008).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…This is an interesting result by itself, as it demonstrates that learning about features of a novel concept can be achieved by presenting the respective novel words in the context of natural sentences, thereby extending the findings by Ouyang et al (2017) to another, more naturalistic learning scenario. Remarkably, this learning occurs even if the novel words do not directly correspond to an actual concept with which the learner already has experience, but they are instead textual chimeras created from two category members (Lazaridou et al, 2017). This result supports the distributional hypothesis that word meanings are at least partially determined by the linguistic context the words occur in (Harris, 1954;Landauer & Dumais, 1997;Lund & Burgess, 1996;Sahlgren, 2008).…”
Section: Discussionsupporting
confidence: 59%
“…However, our learning phases were also not shorter than those in similar studies that found learning effects on variables such as categorization performances and similarity judgements (Lazaridou et al., ; Ouyang et al., ). This, in combination with the fact that participants were able to make correct judgements in the explicit judgement task, leads us to the assumption that the learning phases we employed were long enough to form a representation for the novel words that is clear enough to perform a variety of different tasks (Lazaridou et al., ; Ouyang et al., ). In fact, in none of the learning phases did the participants get any explicit information about the vertical location of the novel words they learned, but only encountered them in linguistic contexts implying a certain vertical location.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations